2018
DOI: 10.21608/adjalexu.2018.57605
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Using Platelet Concentrates in the Management of Horizontal Ridge Defects (Experimental Study)

Abstract: INTRODUCTION:The use of platelet concentrates remains controversial. Several techniques for platelet concentrates are available and each method leads to a different product with different biology and potential uses. Platelet rich fibrin (PRF) is an autologous biomaterial composed of a fibrin clot matrix entrapping leukocytes, cytokines, living progenitor cells, and platelets capable of releasing various growth factors. One of the recent platelet concentrates is the mineralized plasmatic matrix (MPM) which has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…This study showed the platelet concentrates have no effect on bone dimension (height and width) which is agreed with Anwar et al (16) , which concluded in a histological split mouth design in an experimental study the MPM and PRF showed a good quality of bone but better in MPM.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study showed the platelet concentrates have no effect on bone dimension (height and width) which is agreed with Anwar et al (16) , which concluded in a histological split mouth design in an experimental study the MPM and PRF showed a good quality of bone but better in MPM.…”
Section: Discussionsupporting
confidence: 91%
“…In comparison between the two groups according to density, the both groups show a statistically significant difference in mean density, but MPM group showing a higher bone density than PRF group. Which is agreed with Jean Périssé (9) in his histological study and Anwar et al (16) .…”
Section: Discussionsupporting
confidence: 89%
“…In each dog, four critical-sized horizontal alveolar ridge defects were created preserving the lingual walls. The dimensions of all defects were standardized to be about 7 mm mesio-distally, 8 mm apicocoronally and 5 mm bucco-lingually (21,22). With the aid of rotary burs, bone was removed with thourough irrigation using sterile saline to avoid overheating.…”
Section: Study Design and Groupingmentioning
confidence: 99%